Bottle sealed and wrapped in cloth for better storage - Mumbai Archive Project Team (Jio Institute, 2024)
In the final steps, the bottle is sealed with a cap, tightly wrapped in cloth and tied with a string. East Indian families recall a time not so long ago when they collected empty beer bottles to be repurposed for storing masala. Over time, glass bottles have been phased out and replaced with airtight containers, which can store larger quantities and are easy to stack. Bottles are still used, although sparingly.